IMPROVING INTENSIVE READING SKILLS WITH THE KNOW WANT TO KNOW LEARNED STRATEGY - Marlina Eliyanti Simbolon; Lestrari Putri Aditaeni (Kopertis Region IV Jabar and Banten, 2023)
The problem in this study is the low intensive reading skills of students in Indonesian content which is below the KKM. This study aims to describe the difference in the effect of the intensive reading skills of students in the experimental class who received the Know Want To Know Learned learning strategy and the control class who did not receive the Know Want To Know Learned learning strategy and to describe the differences in the improvement of intensive reading skills of the experimental class students who used the strategy. Know Want To Know Learned learning with a control class that does not use the Know Want To Know Learned learning strategy. The method used is Quasi-Experimental, and the research design is Nonequivalent Control Group Design. The research subjects were 41 students of class V SD Negeri Cigarukgak. The instrument used in this research is a description test. The results showed that the posttest results were greater than the pretest results. There are differences in students' intensive reading skills after being given treatment using the Know Want To Know Learned learning strategy. The difference in increasing intensive reading skills can be seen from the results of the n-gain test, namely the medium category to the high category. There is a difference in the increase in students' intensive reading skills using the Know Want To Know Learned learning strategy.